REVENUE ANALYSIS USING BREAK EVEN POINT IN ANGEL LAUNDRY - Ninda Nur Fauziah, Ninda Nur Fauziah; Wehdawati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Break even point is the condition of a business that does not earn a profit and does not suffer loss. The purpose of this study was to determine Angel Laundry’s sales revenue at Kuala Pembuang using a break even point. The method used is descriptive method.The results showed a break even point in units of 179,29 kg per month. In addition, Angel Laundry’s efforts are right in determining the selling price of Rp 6.000 per kg when viewed from the value of break even point (rupiah), so to get a business profit Angel Laundry must be able to get the above sales from Rp 1.070.772. In May 2019 Angel Laundry’s business was able to sell 830 kg of laundry services. Based on the above analysis results obtained sales in May 2019 of Rp 4.980.000 and the results of the break even point rupiah amounting to Rp 1.070.772 means that Angel Laundry’s business gets a profit of Rp 3.909.228 or 78,49%.